Kesulitan Yang Dirasakan Sendiri (Self – Perceived Difficulty) Dalam Melakukan ADL (Activity Of Daily Living) Pada Pasien Strok Iskemik di Rumah Sakit Umum Banda - Yulianti Ely (Lembaga Pengembangan Kinerja Dosen, 2025)
Stroke is one of the leading causes of long-term disability worldwide. Stroke survivors often experience severe disabilities, particularly in their ability to walk and perform daily physical activities independently. Many are unable to ambulate without assistance, even after reaching a certain level of independence. These persistent impairments contribute to a decreased quality of life and increase the risk of long-term complications. This study aims to determine the self-perceived difficulty in performing Activities of Daily Living (ADL) among ischemic stroke patients. The research employed a quantitative descriptive design and involved 25 ischemic stroke patients selected through purposive sampling. Data were collected at Banda General Hospital using the Barthel Index (BI) assessment tool to evaluate the patients' level of independence in carrying out daily activities, both before and after receiving physiotherapy. The results showed that, prior to physiotherapy, 10 respondents (40%) were in the category of severe dependency, requiring significant assistance to perform ADL. Following physiotherapy intervention, there was a decrease in the number of patients in the severe dependency category, indicating an improvement in functional independence. These findings suggest that physiotherapy plays an important role in supporting recovery and enhancing the ability of ischemic stroke patients to carry out daily activities. Patients’ self-perceived difficulties are also essential indicators in designing more personalized and effective rehabilitation programs.